2012
DOI: 10.1093/annonc/mds210
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters model for predicting pathologic complete response following preoperative chemoradiation in patients with esophageal cancer

Abstract: Our data suggest that the logistic regression model can predict pathCR with a high probability. This clinical model could complement others (biomarkers) to predict pathCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 28 publications
3
64
3
Order By: Relevance
“…In concordance with the literature, this data demonstrate that female gender and SCCs are the strongest pre-treatment predictive factors for pCR (10,14,(26)(27)(28). However the number of females with SCC is too small in this cohort to confirm this with a significant better OS outcome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In concordance with the literature, this data demonstrate that female gender and SCCs are the strongest pre-treatment predictive factors for pCR (10,14,(26)(27)(28). However the number of females with SCC is too small in this cohort to confirm this with a significant better OS outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that pCR is independently associated with survival, both the 5-year OS and disease free survival (6,8,9). In literature, squamous cell carcinoma (SCC) and female gender are identified as predictive factors for pCR (8,(10)(11)(12)(13)(14), there is however limited knowledge on factors that can be used to predict which patients will achieve a pathologic non response (pNR). The effect of nCRT in patients with a pNR remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Identification of a molecular or histologic marker that is that predicts pCR following CRT would provide useful adjunctive clinical information, although others have attempted to predict clinical surrogates for benefit from CRT. 22 It is worth noting that based on our model, even patients with a heavy residual disease burden demonstrated on pathology after CRT received a survival benefit from their trimodality treatment when compared with patients with comparable pathologic stage undergoing isolated esophagectomy. We predict that a typical patient with ypT4N3 disease received an estimated 9-month median survival benefit from their CRT, irrespective of their clinical stage of disease.…”
Section: Recent Randomized and Appropriately Powered Clinical Data Comentioning
confidence: 86%
“…13,14 Approximately 5 to 6 weeks after the completion of chemoradiotherapy, the patients underwent preoperative restaging. All patients completed esophagectomy.…”
Section: Therapymentioning
confidence: 99%